Relationships between executive function of children in residential care and caregivers’ discipline style: a pilot study. - Gaitán, Sabina D.; Fernández-Baena, Francisco Javier; Salas-Martínez, María Dolores (My University, 2024)
Despite legislative efforts to ensure that the Residential Care (RC) guarantees good care for children, there are difficulties inherent to the profile of the foster population. One of the areas affected in this population is executive functions. However, there is a lack of information on how these functions are related to other variables as affective relationships (affection/communication and criticism/rejection) and the discipline styles of caregivers. Therefore, this research aims to study these relationships. Forty-six boys and girls between 10 and 16 years old and thirty-nine caregivers from seven residential centres participated in the study. This work is a pilot study within a larger research that includes all the RC centres in the province of Malaga (Spain). BRIEF-2 Family version was used to assess executive functions, while Warmth Scale (EA) and the Rules-Demands Scale (ENE) were used to asses affection and discipline style of caregivers. The results showed that: (a) about 50% of the sample shows scores classified as high or clinically significant on all scales and indexes of executive functions, while the general Spanish population shows only 16-19% in this same categories, (b) higher scores on perceived criticism/rejection show a postive correlation with difficulties in emotional and cognitive control, and (c) an indulgent/permissive discipline style is positively correlated to cognitive control problems. These results are not conclusive, as they correspond to the pilot study phase, nevertheless they already point to the need of deeper research about the difficulties presented by the population in RC in terms of executive functions.
Keywords: Centros de acogida de menores - Málaga; Niños - Cuidados institucionales - Aspectos psicológicos; Executive function; Discipline style; Residential care